Grid-connected battery energy storage system using interleaved bidirectional buck/boost converter and 3-level SVPWM inverter - Oumaymah Elamri; Jacob Wekalao (Institute of Advanced Engineering and Science, 2026)
This study presents a high-performance grid-connected battery energy storage system architecture designed to overcome the trade-off between DC-side current ripple and AC-side power quality. The proposed system synergistically integrates an interleaved bidirectional buck/boost converter, a three-level neutral-point clamped inverter, and an optimized LCL filter under a unified control strategy based on space vector pulse width modulation. Unlike conventional topologies that prioritize either subsystem individually, this integrated approach simultaneously minimizes battery current stress and ensures strict grid compliance. Extensive simulations in MATLAB/Simulink demonstrate that the proposed control strategy achieves a total harmonic distortion (THD) of just 2.93%, significantly outperforming the 40.25% THD of conventional two-level inverters and surpassing recent state-of-the-art benchmarks. The system exhibits robust dynamic response during rapid charging/discharging transitions and maintains stability under grid disturbances, such as 20% voltage dips. These results validate the architecture as a viable, high-efficiency solution for integrating modern renewable energy.